Cerebral metabolic correlates of attention networks in Alzheimer's Disease: A study of the Stroop. (November 2017) - Melrose, Rebecca J.; Young, Stephanie; Weissberger, Gali H.; Natta, Laura; Harwood, Dylan; Mandelkern, Mark; Sultzer, David L.
Abstract: Patients with Alzheimer's Disease (AD) show difficulties with attention. Cognitive neuroscience models posit that attention can be broken down into alerting, orienting, and executive networks. We used the Stroop Color-Word test to interrogate the neural correlates of attention deficits in AD. We hypothesized that the Word, Color, and Color-Word conditions of the Stroop would all tap into the alerting and orienting networks. The Color-Word condition would additionally tap into the executive network. A ratio of Color-Word to Color naming performance would isolate the executive network from the others. To identify the neural underpinnings of attention in AD we correlated performance on the Stroop with brain metabolic activity. Sixty-six patients with probable AD completed [ 18 F] fluorodeoxyglucose PET scanning and neuropsychological testing. Analysis was conducted with SPM12 (p<0.001 uncorrected, extent threshold 50 voxels). Performance on the Word, Color, and Color-Word conditions directly correlated with metabolic rate in right inferior parietal lobules/intraparietal sulci. The Color-Word/Color ratio revealed associations with metabolic rate in right medial prefrontal cortex and insula/operculum. Overall findings were largely consistent with the hypothesized neuroanatomical substrates of the alerting, orienting, and executive networks. As such, attention deficits in AD reflect compromise to multiple large-scale networks. Highlights: The Stroop test measures word reading, color naming, and interference. Hypometabolism of inferior parietal lobe predicts poor performance on all conditions. Interference is associated with metabolic rate in medial PFC and insula. AD is characterized by hypometabolism in alerting, orienting, and executive networks.